Respuesta :

Answer:

Hence, in the simplification of [tex](y -3)(y^2 +3y + 9)[/tex] the value of a  = 9.

Step-by-step explanation:

Here, the given expression is [tex](y -3)(y^2 +3y + 9)[/tex]

Simplify this given expression, we get:

[tex](y -3)(y^2 +3y + 9)  = y)(y^2 +3y + 9)  -3(y^2 +3y + 9)\\= y(y^2) + y(3y)  + y(9)   -3(y^2) -3(3y) -3(9)\\=y^3 + 3y^2 + 9y - 3y^2 -9y  - 27\\\implies y^3  - 27  = 0\\[/tex]

Now, the given expanded form is [tex]y^3 + 3y^2 + ay - 3y^2 -ay  - 27[/tex]

Comparing it with given second last step in simplification, we get

[tex]y^3 + 3y^2 + ay - 3y^2 -ay  - 27  = y^3 + 3y^2 + 9y - 3y^2 -9y  - 27[/tex]

Comparing all term on both sides, we get

ay =  9y

and -ay =  -9y

⇒ a = 9 on both sides.

Hence, in the simplification of the polynomial, the value of a  = 9.

ACCESS MORE